A Bacteriophage-Loaded Microparticle Laden Topical Gel for the Treatment of Multidrug-Resistant Biofilm-Mediated Burn Wound Infection - Dehari D.; Chaudhuri A.; Kumar D.N.; Anjum M.; Kumar R.; Kumar A.; Kumar D.; Nath G.; Agrawal A.K. (My University, 2025)
Klebsiella pneumoniae is regarded as one of the most profound bacteria isolated from the debilitating injuries caused by burn wounds. In addition, the multidrug resistance (MDR) and biofilm formation make treating burn patients with clinically available antibiotics difficult. Bacteriophage therapy has been proven an effective alternative against biofilm-mediated wound infections caused by MDR bacterial strains. In the current study, the bacteriophage (BPKPФ1) against MDR Klebsiella pneumoniae was isolated and loaded into the chitosan microparticles (CHMPs), which was later incorporated into the Sepineo P 600 to convert into a gel (BPKPФ1-CHMP-gel). BPKPФ1 was characterized for lytic profile, morphological class, and burst size, which revealed that the BPKPФ1 belongs to the family Siphoviridae. Moreover, BPKPФ1 exhibited a narrow host range with 128 PFU/host cell of burst size. The BPKPФ1-loaded CHMPs showed an average particle size of 1.96 ± 0.51 μm, zeta potential 32.16 ± 0.41 mV, and entrapment efficiency in the range of 82.44 ± 1.31%. Further, the in vitro antibacterial and antibiofilm effectiveness of BPKPФ1-CHMPs-gel were examined. The in vivo potential of the BPKPФ1-CHMPs-gel was assessed using a rat model with MDR Klebsiella pneumoniae infected burn wound, which exhibited improved wound contraction (89.22 ± 0.48%) in 28 days with reduced inflammation, in comparison with different controls. Data in hand suggest the potential of bacteriophage therapy to be developed as personalized therapy in case of difficult-to-treat bacterial infections. Graphical abstract: [Figure not available: see fulltext.]. © 2023, The Author(s), under exclusive licence to American Association of Pharmaceutical Scientists.